Retroperitoneal-first laparoscopic approach (Retlap)-assisted distal pancreatectomy with celiac axis resection (DP-CAR): A novel minimally invasive approach for achieving adequate dorsal surgical margin. (May 2022) - Kiguchi, Gozo; Sugioka, Atsushi; Kato, Yutaro; Uyama, Ichiro
Abstract: Background: Distal pancreatectomy with celiac axis resection (DP-CAR) is a procedure to secure a surgical margin for a locally advanced pancreatic body cancer that invades the celiac axis. However, in patients with cancer close to the root of the celiac axis, obtaining adequate surgical margins can be difficult because the tumor obstructs the field of vision to the root of the celiac axis. Previously, we described the retroperitoneal-first laparoscopic approach (Retlap) to achieve both accurate evaluation of resectability for locally advanced pancreatic cancer requiring DP-CAR [1 ] and adequate surgical margin for laparoscopic distal pancreatectomy [2 ]. In this video, we introduce Retlap-assisted DP-CAR as a minimally invasive approach for performing an artery-first pancreatectomy [3, 4 ] and achieving sufficient dorsal surgical margin (Fig. 1 ). Methods: Our patient is a 67-year-old man with a 55 × 29-mm pancreatic body tumor after chemotherapy. Preoperative computed tomography revealed a tumor close to the root of the celiac axis. Because the area of tumor invasion on preoperative images was near the root of the celiac artery, Retlap-assisted DP-CAR was performed to determine whether the celiac axis can be secured and obtain an adequate dorsal surgical margin (Fig. 2 ). Results: The operative time and estimated blood loss was 715 min and 449 mL, respectively. In spite of the advanced tumor's location and size, R0 resection was achieved in a minimally invasive way. Conclusion: Retlap-assisted DP-CAR is not only technically feasible and useful for achieving accurate evaluation of resectability but also facilitates obtaining an adequate surgical margin. Highlights: Tumor location affects obtaining adequate dorsal surgical margin in DR-CAR. This video demonstrates Retlap-assisted DP-CAR for advanced pancreatic body cancer. Minimally invasive Retlap-assisted DP-CAR secures the root of the celiac axis. This approach facilitates obtaining an adequate dorsal surgical margin.